Two-inductor non-isolated dc-dc converter with high step-up voltage gain - Lee, Sze Sing; Chu, Bing; Lim, Chee Shen; Lee, Kyo Beum (Journal of Power Electronics, 2019)
In this paper, an alternative non-isolated DC-DC converter with a high voltage boosting capability is proposed. Two inductors are used and one of them has its flux linkage increases during its charging period to achieve a high step-up voltage gain. Among the three integrated capacitors, one portrays the partial characteristic of the switched-capacitor technique, while the other two are connected in series across the load. With the two switches controlled using the same duty cycle, the proposed topology demonstrates the merits of a higher and wider range of step-up voltage gain when compared with recent topologies. In addition, a reduction in loss is induced and a higher efficiency is ensured with all the voltage stresses constrained within the output voltage. Operation of the proposed converter is analyzed and validated through experimental results obtained with a prototype.
Keywords: High step-up voltage gains; High step-ups; Higher efficiency; Integrated capacitors; Isolated dc-dc converters; Non-isolated; Switched capacitor techniques; Two inductors; Dc-dc converter; High step-up gain; Non-isolated; Two-inductor